Peran Generasi Muda dalam Pemilihan Kepala Desa di Desa Kaban Tengah Kecamatan STU Jehe Kabupaten Pakpak Bharat - Rini Armianti Berutu; Julia Ivanna (Journal on Education, 2024)
The article is titled "The Role of Youth in the Village Head Election in Kaban Tengah Village, STU Jehe District, Pakpak Bharat Regency." This article aims to describe the role of youth in the village head election in Kaban Tengah Village, STU Jehe District, Pakpak Bharat Regency. The research method used is descriptive qualitative. Based on the research results, the author found that the youth's participation in the village head election in Kaban Tengah Village is influenced by socio-political agents, such as family, peer groups, schools, workplaces, mass media, and direct political contact. The dissemination and introduction of elections to the youth in Kaban Tengah Village are carried out by socializing the importance of elections to the youth, conducted by the KPU and the government of Pakpak Bharat Regency. Youth is very important to ensure the realization of a democratic and integrity-filled election process in Kaban Tengah Village.